The impact of digital technology on the development of public television in the Kyrgyz Republic - Kaparova, Ч. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2021)
The globalisation of the world and the unprecedented technological processes taking place within it have caused great changes in the field of television as well. These innovations have made it necessary to study them. The article explores new phenomena in the field of TV and analyses the mechanisms of media market transformation. An attempt has been made to reveal the achievements and problems in the process of converting Kyrgyzstan’s TV channels to digital format. The author has tried to find an answer to the question of how domestic television, gaining international experience, can improve its performance and be competitive.